Letter : Spain - deputation to Prime Minister - Willis, Robert
012b-0066-001 Established 1860 Affiliated Membership over 300,000 TELEPHONE CENTRAL 5622 LONDON TRADES COUNCIL Secretary: ROBERT WILLIS To whom all communication should be addressed Cheques should be made payable to: "The London Trades Council" 24, Thavies Inn, Holborn, London E.C.1. 20th January 1939 Mr. H.V. Tewson, Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, Spain - Deputation to Prime Minister. Thank you for your letter of yesterday's date with reference to the above. I note that the subject is to be further discussed at the National Council of Labour on Tuesday next. Yours sincerely, Robert Willis Secretary 292/946/12b/66